Development of multi-parameter fibre optic chemical sensor system based on long period gratings modified with the functional thin films - Hromadka, Jiri (2017)
This work focuses on the development of fibre optic long period grating (LPG) based chemical sensors and the fabrication and evaluation of the appropriate sensitive coatings.